Author’s Index; a new tool to compare scholars - Sorooshian, Shahryar (2017)
Our inovation is in developing a new index, Author’s Index (Aindex), for comparison between scholars. Comparison of scholars is a need for performance appraisal in scientific communities. The A-index is an author-level metric that attempts to measure both the productivity and citation impact of the publications of a scientist or scholar. The index is based on the set of the scientist's most cited papers and the number of citations that they have received in other publications. The A-indexed minimize the disadvantages of current available indexes. The A-index is useful for academicians management in universities